EVALUASI RISIKO CEDERA MUSCULOSCELETAL BERBASIS METODE RULA DAN REBA PADA OPERATOR BAGIAN PENGIRIMAN BARANG DI PT DCF - Dhonny, Mohammad Ahsantudh; Mahbubah, Nina Aini (SIGMA TEKNIKA, 2025)
This study aims to evaluate the risk of Musculoskeletal Disorders (MSDs) during manual material handling activities at Firm DCF's warehouse. Tasks such as lifting, moving, and arranging goods manually can cause risk due to non-ergonomic postures. The research began with observation and Nordic Body Map (NBM) questionnaires, followed by posture analysis using the Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA) methods. The results indicate that the highest risk occurs during receiving and picking activities, with REBA scores of 11 and RULA scores of 7. This result shows the need for immediate corrective action. The primary contributing factors are bending postures, heavy loads, and repetitive movements. Recommended improvements include providing training on proper lifting techniques, using mechanical aids such as hand pallets or trolleys, and adjusting rack heights to match optimal reach distances. Implementing ergonomic risk principles is expected to reduce injury risks, enhance work comfort, and sustain productivity among warehouse employees at PT DCF.